(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Most women who use contraception are fit and healthy. However; some health conditions may be associated with real or theoretical risks if a particular contraceptive method affects the health condition. In an attempt to produce a set of international norms for providing contraception to individuals with a range of medical conditions that may contraindicate a contraceptive method, the World Health Organization (WHO) developed medical eligibility criteria for contraceptive use.